Biotherapeutic Antibodies for the Treatment of Head and Neck Cancer: Current Approaches and Future Considerations of Photothermal Therapies - Al Qaraghuli, Mohammed M. (Frontiers in Oncology, 2020)
Head and Neck Cancer (HNC) is a heterogeneous disease that includes a variety of tumors originating in the hypopharynx, oropharynx, lip, oral cavity, nasopharynx, or larynx. HNC is the sixth most common malignancy worldwide and affects thousands of people in term of incidence and mortality. Various factors can trigger this disease such as smoking, alcohol consumption, and repetitive viral infections. HNC is currently treated by a single or multi-modality approaches, which are based on surgery, radiotherapy, chemotherapy, and biotherapeutic antibodies. The latter approach will be the focus of this article. There are currently three approved antibodies against HNCs (Cetuximab, Nivolumab, and Pembrolizumab), and 48 antibodies under developments. The majority of these antibodies were of humanized (23 antibodies) or human (19 antibodies) origins, and subclass IgG1 has represented a total of 32 antibodies. In addition, three antibody drug conjugates (ADCs: Telisotuzumab-Vedotin, Indatuximab-Ravtansine, and W0101) and two bispecific antibodies (GBR 1372 and ABL001) have been under development. Despite the remarkable success of antibodies in treating different tumors, however, this success was limited in HNCs. This limitation is attributed to efficacy, resistance, and the appearance of various side effects. However, the efficacy of these antibodies could be enhanced through conjugation to gold nanoparticles (GNPs). These conjugates combine the high specificity of antibodies with unique spectral properties of GNPs to generate a treatment approach known as photothermal therapy. This approach can provide promising outcomes due to the ability of GNPs to convert light into heat, which can specifically destroy cancer cells and treat HNC in an effective manner.